Treat to target in Behcet's disease: Should we follow the paradigm of other systemic rheumatic diseases - MUMCU, GONCA (My University, 2022)
During the last decades the efficacy of biologic agents, mainly of anti-TNFs, in controlling the activity of serious manifestations of Behcet’s Disease (BD) has been established. On the other hand, the clinical heterogeneity of BD has precluded the validation of a widely-accepted composite index for disease assessment and for target diseasestate definitions, such as low disease activity and remission, and the testing of their implementation in clinical practice. Therefore, in contrast to other systemic rheumatic diseases, a treat-to-target strategy has not yet been developed in BD. There are several challenges towards this approach, including standardization of outcome measures for assessing the disease activity in each-affected organ and construction of a composite disease activity index. The challenges for the development of a treat-to-target strategy and possible solutions are discussed in this position paper, which stemmed from a round table discussion that took place in the 19th International Conference on BD.
Keywords: Behcet's disease; Disease activity; Treat-to-target